Evaluasi Kebijakan Penyaluran Pupuk Bersubsidi Berdasarkan Permentan Nomor 01 Tahun 2024 di Kabupaten Jombang - Villa Makhtunin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Agriculture plays a crucial role in Indonesia's economy and food security, with subsidized fertilizers being a vital component in supporting productivity and the quality of harvests. The subsidized fertilizer policy, as regulated in Minister of Agriculture Regulation No. 01 of 2024, aims to ensure the targeted distribution of fertilizers. However, issues related to distribution and the misuse of subsidized fertilizers remain significant challenges. This study aims to evaluate the implementation of the subsidized fertilizer distribution policy in Jombang Regency based on Minister of Agriculture Regulation No. 01 of 2024. Using a qualitative descriptive approach, the research gathered data through interviews with informants, observations, and documentation at the Agriculture Office of Jombang Regency. The findings show that although the e-RDKK system has improved farmers' access to subsidized fertilizers, administrative barriers and distribution delays remain major issues. Uneven distribution coverage and the misallocation of fertilizers in several areas reduce the policy's effectiveness. Improvements in distribution management and stricter supervision are necessary to ensure the sustainability of the agricultural sector and food security in Jombang Regency. The distribution of subsidized fertilizers in Jombang Regency needs to be improved through more intensive education for farmers and simplification of administrative procedures.